Station Eleven : a novel - Mandel, Emily St. John, 1979- (Knopf, 2014)
"An audacious, darkly glittering novel about art, fame, and ambition set in the eerie days of civilization's collapse, from the author of three highly acclaimed previous novels. One snowy night a famous Hollywood actor slumps over and dies onstage during a production of King Lear. Hours later, the world as we know it begins to dissolve. Moving back and forth in time-from the actor's early days as a film star to fifteen years in the future, when a theater troupe known as the Traveling Symphony roams the wasteland of what remains-this suspenseful, elegiac, spellbinding novel charts the strange twists of fate that connect five people: the actor, the man who tried to save him, the actor's first wife, his oldest friend, and a young actress with the Traveling Symphony, caught in the crosshairs of a dangerous self-proclaimed prophet. Sometimes terrifying, sometimes tender, Station Eleven tells a story about the relationships that sustain us, the ephemeral nature of fame, and the beauty of the world as we know it"--